The Tumor Suppressor Role of Zinc Finger Protein 671 (ZNF671) in Multiple Tumors Based on Cancer Single-Cell Sequencing - Zhang, Jian; Luo, Jianli; Jiang, Huali; Xie, Tao; Zheng, Jieling; Tian, Yunhong; Li, Rong; Wang, Baiyao; Lin, Jie; Xu, Anan; Huang, Xiaoting; Yuan, Yawei (Frontiers in Oncology, 2019)
In humans, zinc finger protein 671 (ZNF671) is a type of transcription factor. However, the contribution of tumor heterogeneity to the functional role of ZNF671 remains unknown. The present study aimed to determine the functional states of ZNF671 in cancer single cells based on single-cell sequencing datasets (scRNA-seq). We collected cancer-related ZNF671 scRNA-seq datasets and analyzed ZNF671 in the datasets. We evaluated 14 functional states of ZNF671 in cancers and performed ZNF671 expression and function states correlation analysis. We further applied t-distributed stochastic neighbor embedding to describe the distribution of cancer cells and to explore the functional state of ZNF671 in cancer subgroups. We found that ZNF671 was downregulated in eight cancer-related ZNF671 scRNA-seq datasets. Functional analysis identified that ZNF671 might play a tumor suppressor role in cancer. The heterogeneous functional states of cell subgroups and correlation analysis showed that ZNF671 played tumor suppressor roles in heterogeneous cancer cell populations. Western blot and transwell assays identified that ZNF671 inhibited EMT, migration and invasion of CNS cancers, lung cancer, melanoma, and breast carcinoma in vitro. These results indicated that the ZNF671 played a tumor suppressor role in multiple tumors based on cancer single-cell sequencing, which may provide us with new insights into role ZNF671 for cancer treatment.